(untitled) (Research, Society and Development, 2020)
Several biological contaminants, such as microorganisms and parasites, can be found in food and affect the health of consumers. The demand for minimally processed foods is increasing, including fruit salads that are sold by street vendors. The objective of this research was to evaluate microorganisms, parasites, and nonbiological contaminants in minimally processed fruit salads sold by street vendors. Fifty fruit salad samples marketed by different street vendors were randomly collected. Presence of Salmonella spp. was found in 2% of the samples. High number of microorganisms of the coliform group was found; Escherichia coli was found in 10% of the samples, growth of coagulase-positive staphylococcus was found in 14% of the samples, and molds and yeasts in the samples ranged from 3.77 to 7.78 log10CFU g-1. No parasites or nonbiological contaminants were found in any sample analyzed. The salad samples presented microbial contamination and represent risks to the health of the consumers due to the possibility of transmitting pathogenic microorganisms of importance to public health.